Raising US$23 Trillion : Greening Banks and Capital Markets for Growth - Kludovacz, Tibor; Stein, Peer; Rooprai, Gursimran (International Finance Corporation, Washington, DC, 2018)
In December 2015, at the Conference of the Parties 21 (COP 21) in Paris, France, 196 countries came together to forge a climate change agreement that pledged to keep global warming to 2 degrees Celsius or less. To bring the world to this 2-degree track, the international energy agency estimates that the cumulative investments needed in energy supply and efficiency reach United States (U.S.) 53 trillion dollars. Based on the International Finance Corporation (IFC) analysis of U.S. 23 trillion dollars in climate-smart investment opportunities in emerging markets between 2016 and 2030, this paper analyzes the role of the banking sector and debt capital markets to provide the financing necessary. Banks will need to rely on debt capital markets to help with the necessary maturity transformation to match primarily longer dated assets with long-term liabilities. The paper concludes with several case studies that showcase how lenders leverage debt capital markets to increase their lending capacity to meet the significant financing needs that the climate transition presents.